EFFECT OF TEXTILE MILL EFFLUENT ON GROWTH AND GERMINATION OF BLACK GRAM - Vigna mungo (L.) Hepper - J. ALBINO WINS; M. MURUGAN (International Journal of Pharma and Bio Sciences, 2010)
The effect of textile effluent was studied with respect to germination and growth of black gram Vigna mungo (L.) Hepper. In lower concentration the germination ratio and growth are relatively higher than the control, but gradual decrease in the germination of seeds, seedling growth with increase in effluent concentration was observed. The best germination and seedling growth was observed in 25% concentration with growth promoting effect, and significantly better than control. Beyond 25% effluent, root and shoot length decreased. Thus the textile mill effluent can be safely used for irrigation purposes with proper treatment and dilution at 25%.